Are consumers satisfied with the use of prosthetic sports feet and the provision process? A mixed-methods study. (October 2020) - Poonsiri, J.; van Putten, S.W.E.; Ausma, A.T.; Geertzen, J.H.B.; Dijkstra, P.U.; Dekker, R.
Abstract: Background: Special feet connected to a prosthesis, prosthetic sports feet, enable athletes with a lower limb amputation to run. The selection of a prosthetic sports feet is usually based on body weight and preferred sports performance. The selection of a prosthetic sport feet is also based on clinicians who likely have limited experience due to a small number of athletes with a lower limb amputation. Hypothesis: Athletes with a lower limb amputation are not satisfied with the use and service associated with prosthetic sports feet due to a lack of prosthetic sports feet provision guidelines, poorer function of prosthetic sports feet compared to the anatomical foot and ankle, and limited experience of clinicians. Evaluation of hypothesis: A mixed-methods study in 16 athletes with a lower limb amputation using a prosthetic sport foot from Össur or Otto Bock, included semi-structured interviews and quantitative analysis. Three dimensions of prosthetic sports feet were investigated: 1) use, 2) provision process, and 3) cosmetics. Qualitative data were analyzed to identify factors influencing consumer satisfaction. Quantitative data were analyzed to investigate satisfaction and perceived relative importance of the dimensions. Results: Participants were satisfied with the prosthetic sports feet use. However, they were not satisfied with the process prior to provision. The prosthetic sport feet use was perceived as the most important dimension. Sports performance was the critical element in the prosthetic sports feet use and was influenced by stability, confidence and fear, safety, focus, energy return, and comfort. Cosmetics were unimportant. Motivation to purchase the prosthetic sports feet was the key element for the prosthetic sports foot acquisition. Satisfaction about the process prior to provision was negatively influenced by poor support of professionals during rehabilitation, the complexity and duration of the purchase process, and lack of information and accessibility of prosthetic sports feet. Conclusion: The most important dimension of the prosthetic sports feet was its use, which was directly influenced by performance. To further increase the satisfaction with prosthetic sports feet, clinicians should establish how to meet the desired sports performance level of athletes with a lower limb amputation. Improving the process prior to the provision process may increase satisfaction. We suggest increasing the support of professionals during rehabilitation and training through cooperation between involved services, organizing prosthetic sports feet try-out sessions, and increase the accessibility of the prosthetic sports feet. In this way, individuals with a lower limb amputation may become and stay more physically active and participate in sports.